Palladium-Catalyzed Thiocarbonylations with Triisopropylsilyl Thioethers - Hosoya, Yosuke; Mizoguchi, Kota; Yasukochi, Honoka; Nakada, Masahisa (Synlett, 2022)
We have developed a palladium-catalyzed thiocarbonylation through the reaction of a σ-alkyl palladium intermediate with carbon monoxide and a triisopropylsilyl (TIPS) thioether. The use of CsF, (IPr)Pd(allyl)Cl [IPr =1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene], CO, and a TIPS thioether in THF are key to obtaining alkyl and aryl thioesters in high yields. The yield of the palladium-catalyzed thiocarbonylation depended on the structure of the substrate; indoline-2-one derivatives were formed faster than indoline derivatives. The reactions of benzoyl and hydrocinnamoyl fluorides with TIPSSPh and CsF also gave the corresponding thioesters.
Keywords: palladium catalysis; thiocarbonylation; thioethers; thioesters; acyl fluorides